Male vs. female EFL students: Who is better in speaking skill? - Nira Erdiana; Syamsul Bahri; Cut Nurul Akhmal (Universitas Syiah Kuala, 2019)
This research is aimed to investigate whether or not female EFL students' ability in speaking skill is better than male students. It deals with the hypothesis that mentions female students are better than male students in speaking skill. The method applied is the descriptive quantitative approach in which ten male and ten female students of the first grade of one of the high schools in Banda Aceh, Indonesia, become randomly the samples. The speaking test is done in order to collect the data and it is conducted to identify the male and female ability in English speaking skill, especially in the five aspects of speaking skill: pronunciation, grammar, fluency, comprehension, and vocabulary. The results show that the females actually dominate the higher scores in all aspects of speaking, however, the mean scores of male and female students are relatively similar, female students reach 68.5 while male students reach 63.3. The t-test is lower than t-table (-1.671.72), which means that the alternative hypothesis (Ha) of this study is rejected and the null hypothesis (Ho) is accepted. Therefore, it can be inferred that the first-grade female students of the high school under study have better performance in speaking skill than the male students, despite the difference is trivial.